The Science of Climate Change - Weaver, Andrew (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2003)
Summary Central to the findings of the Intergovernmental Panel on Climate Change (IPCC) third assessment report, released in Shanghai in January 2001, was the statement: "There is now new and stronger evidencethat most of the warming observed over the last 50 years is attributable to human activities."This represents a significant strengthening of the analogous statement issued by the IPCC in 1996: "The balance of evidence suggests a discernible human influence on global climate" In this article the scientific evidence leading up to these IPCC statements is reviewed. A historical perspective of the Earth's climate over the last 400,000 years is presented, as is the science of global warming over the last 200 years. The range of projections of climate change over the next century is also summarized giving particular emphasis to projections concerningCanada. The issue of uncertainty in climate change projections is tackled and the public confusion arising from the media portrayal of the science and its entry into the political arena discussed. Finally, The Kyoto Protocol and how it fits within the framework of necessary actions required to reduce greenhouse gas emissions is reviewed.